New Occurrence of Pyroxenites in the Veria-Naousa Ophiolite (North Greece): Implications on Their Origin and Petrogenetic Evolution - Aikaterini Rogkala; Petros Petrounias; Basilios Tsikouras; Konstantin Hatzipanagiotou (Geosciences, 2017)
The Veria-Naousa ophiolite represents a dismembered unit in north Greece, which includes variably serpentinised lherzolite and harzburgite, locally intruded by a sparse network of dykes or thin layers of websterite and olivine-orthopyroxenite composition. The websterite and the olivine-orthopyroxenite show abundant petrographic and geochemical evidence (relic olivines with mantle affinities, Cr-rich spinels, low Al2O3, depletions in incompatible elements, and concave upwards rare earth element patterns) that they comprise replacive bodies from refractory subarc mantle precursors. The occurrence of these pyroxenites in dykes implies that channelled percolation of melts account for their replacive character. High CaO/Al2O3, low Zr and crystallisation of diopside suggest that a melt of ankaramitic/carbonatitic composition percolated in lherzolite replacing porphyroclastic olivine and forming the pyroxenes in the websterite. At a shallower level, harburgites were impregnated by boninitic melts (inferred by U-shape rare earth element patterns and very rich in Cr spinels) triggering the replacement of porphyroclastic olivine by orthopyroxene for the formation of olivine-orthopyroxenite. These peritectic replacements of olivine commonly occur in a mantle wedge regime. The peculiar characteristics of the Veria-Naousa pyroxenites with LREE and compatible elements enrichments resemble the subarc pyroxenites of Cabo Ortegal implying a similar environment of formation. Whole-rock and mineralogical (spinel and clinopyroxene) compositions are also in favour of a backarc to arc environment. It is recommended that the evolution of the Veria-Naousa pyroxenites record the evolution of the subarc region and the opening of a backarc basin in a broad SSZ setting in the Axios Zone of eastern Greece.